Edpuzzle-Based Digital Learning Media for Enhancing Students’ Achievement in Islamic Religious Education - Dewi Nur Jayanti; Anang Sholikhudin; Achmad Yusuf; Saifullah Saifullah (Journal of Educational Management Research, 2026)
This study aims to examine the planning, implementation, and impact of Edpuzzle-based digital media on improving students’ learning outcomes in Islamic Religious Education. This research employed a descriptive qualitative approach with a field research design. The participants consisted of Islamic Religious Education teachers and tenth-grade vocational high school students. Data were collected through observation, in-depth interviews, and documentation, then analyzed using data reduction, data presentation, and conclusion drawing techniques. The validity of the data was ensured through source and technique triangulation. The findings revealed that the planning stage included preparing learning materials, selecting instructional videos, creating digital classrooms, and designing interactive questions integrated into the videos. The implementation of Edpuzzle-based learning successfully created a more interactive, engaging, and student-centered learning environment. The use of Edpuzzle also contributed positively to students’ learning outcomes, as indicated by increased participation, stronger learning motivation, better understanding of learning materials, and improved evaluation results. These findings imply that Edpuzzle can serve as an innovative and effective digital learning medium in Islamic Religious Education.